Developing a contemporary community clinic for patients with heart failure with preserved ejection fraction within the current National Health Service model. Issue 2 (4th November 2022) - Tran, Patrick; Long, Thomas; Smith, Jessica; Kuehl, Michael; Mahdy, Tarek; Banerjee, Prithwish
Abstract : Introduction: The diagnostic and therapeutic arsenal for heart failure with preserved ejection (HFpEF) has expanded. With novel therapies (eg, sodium-glucose co-transporter 2 inhibitors) and firmer recommendations to optimise non-cardiac comorbidities, it is unclear if outpatient HFpEF models can adequately deliver this. We; therefore, evaluated the efficacy of an existing dedicated HFpEF clinic to find innovative ways to design a more comprehensive model tailored to the modern era of HFpEF. Methods: A single-centre retrospective analysis of 202 HFpEF outpatients was performed over 12 months before the COVID-19 pandemic. Baseline characteristics, clinic activities (eg, medication changes, lifestyle modifications, management of comorbidities) and follow-up arrangements were compared between a HFpEF and general cardiology clinic to assess their impact on mortality and morbidity at 6 and 12 months. Results: Between the two clinic groups, the sample population was evenly matched with a typical HFpEF profile (mean age 79±9.6 years, 55% female and a high prevalence of cardiometabolic comorbidities). While follow-up practices were similar, the HFpEF clinic delivered significantly more interventions on lifestyle changes, blood pressure and heart rate control (p<0.0001) compared with the general clinic. Despite this, no significant differences in all-cause hospitalisation and mortality were observed. This may be attributed to the fact that clinic activities were primarily cardiology-focused. Importantly, non-cardiovascular admissions accounted for >60% of hospitalisation, including causes of recurrent admissions. Conclusion: This study suggests that existing general and emerging dedicated HFpEF clinics may not be adequate in addressing the multifaceted aspects of HFpEF as clinic activities concentrated primarily on cardiological measures. Although the small cohort and short follow-up period are important limitations, this study reminds clinicians that HFpEF patients are more at risk of non-cardiac than HF-related events. We have therefore proposed a pragmatic framework that can comprehensively deliver the modern guideline-directed recommendations and management of non-cardiac comorbidities through a multidisciplinary approach.